Academic english in research papers: A stylistic analysis of the texts of sri lankan writers - Jeyaseelan, G. (University of Jaffna, 2020)
Over the last decade, Sri Lankan academics and professionals have shown an increased interest in doing small scale research nationally and regionally. There have been many journals and research conferences in the English medium initiated by the Sri Lankan Universities and professional organizations and societies. They encourage publication and presentation for financial, professional, and humanitarian benefits. Many write the findings of their research and submit. However, apart from the quality and quantity of the research papers, the Academic English quality used in the papers still lacks mastery and fine-tuning. The style of Academic English needs improvement to meet international standards. Mostly it is one of the factors demoting the publications and presentations in the indexed and international journals and conferences. A linguistic approach called stylistic analysis uses the extracted texts of the papers published in business management and finance in the national universities’ conferences in 2019 and 2020 to describe and explain the features and expressions which are not academically standard and suggest appropriate alternatives. It is qualitative. These findings show the implications of wordiness overall. It exemplifies the wrong or low standard academic writing practices in preposition use, punctuation in complex and compound sentences and sentence adverb punctuation, verb-preposition, verb-noun combination in hypothesis formulation, word use, word relations within a sentence, active and passive voice use, diversity in using the types of clauses and phrases, nominalization vs verbalization, adverb and adverbial phrases and clauses, linking words, and diversity in academic vocabulary. Thus this paper creates awareness of efficient and effective Academic English practices in drafting the research papers to meet the standard nationally and internationally.
Keywords: Academic English; Stylistic approach; Redundancy; Sri Lankan research writing; Wordiness